Implementation of Javanese Krama Learning in Improving Students' Ability to Speak Politely at MIMA 35 Nurul Ulum Ambulu - Diana Rahmayanti; Hartono Hartono (EDUCARE: Journal of Primary Education, 2022)
This study examines Javanese Krama's learning in improving students' ability to speak politely at MIMA 35 Nurul Ulum Ambulu. This research approach is a descriptive qualitative approach, and the type of research used is phenomenology. Data collection techniques using interviews, observation, and documentation. While the data analysis using the model of Miles, Huberman, and Johnny Saldana consists of data condensation, data presentation, and conclusion. The results of this study are 1) Planning for learning the Javanese Krama language to improve the ability of students to speak politely at MIMA 35 Nurul Ulum Ambulu, namely: the teacher prepares a Learning Implementation Plan, prepares to memorize material for the Javanese Krama language vocabulary for students. 2) Implementation of Javanese Krama language learning in improving the ability of students to speak politely at MIMA 35 Nurul Ulum Ambulu, namely: opening, core, and closing activities. Then the habit of using Javanese manners during learning hours and outside the classroom. 3) Evaluation of Javanese Krama language learning in improving the ability of students to speak politely at MIMA 35 Nurul Ulum Ambulu, namely: in the classroom using daily questions, PTS and PAS. Meanwhile, habituation outside of learning hours is by assessing students' speech and manners. 4) The implications of learning Javanese Krama in improving the ability of students to speak politely at MIMA 35 Nurul Ulum Ambulu have a positive impact on students becoming accustomed to using Javanese Krama when communicating with teachers both in attitude and speech. Penelitian ini mengkaji mengenai pembelajaran bahasa Jawa Krama dalam meningkatkan kemampuan peserta didik berbicara sopan santun di MIMA 35 Nurul Ulum Ambulu. Pendekatan penelitian ini adalah pendekatan kualitatif deskriptif dan jenis penelitian yang digunakan adalah fenomenologi. Teknik pengumpulan data menggunakan wawancara, observasi dan dokumentasi. Sedangkan analisis data menggunakan model Miles, Hubermen dan Johnny Saldana terdiri dari kondensasi data, penyajian data, dan penarikan kesimpulan. Hasil dari penelitian ini adalah 1) Perencanaan pembelajaran bahasa Jawa Krama dalam meningkatkan kemampuan peserta didik berbicara sopan santun di MIMA 35 Nurul Ulum Ambulu, yaitu: guru menyusun Rencana Pelaksanaan Pembelajaran, menyiapkan materi hafalan kosa kata bahasa Jawa Krama bagi peserta didik. 2) Pelaksanaan pembelajaran bahasa Jawa Krama dalam meningkatkan kemampuan peserta didik berbicara sopan santun di MIMA 35 Nurul Ulum Ambulu, yaitu: kegiatan pembuka, inti, dan penutup. Kemudian pembiasaan berbahasa jawa krama didalam jam pembelajaran dan diluar kelas. 3) Evaluasi pembelajaran bahasa Jawa Krama dalam meningkatkan kemampuan peserta didik berbicara sopan santun di MIMA 35 Nurul Ulum Ambulu, yaitu: di dalam kelas menggunakan soal harian, PTS dan PAS. Sedangkan, pembiasaan di luar jam pembelajaran yaitu dengan penilaian berkaitan dengan tutur kata dan sikap sopan santun peserta didik. 4) Implikasi pembelajaran bahasa Jawa Krama dalam meningkatkan kemampuan peserta didik berbicara sopan santun di MIMA 35 Nurul Ulum Ambulu membawa dampak positif pada peserta didik menjadi terbiasa menggunakan bahasa Jawa Krama saat berkomunikasi dengan guru baik dalam sikap dan tutur kata.